Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine the correct equation for a circle with its center at [tex]\((2, -8)\)[/tex] and a radius of 11, let's use the standard form of the equation for a circle. The formula for the equation of a circle in standard form is:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
where [tex]\((h, k)\)[/tex] is the center of the circle and [tex]\(r\)[/tex] is the radius.
Given:
- The center of the circle [tex]\((h, k)\)[/tex] is [tex]\((2, -8)\)[/tex],
- The radius [tex]\(r\)[/tex] is 11.
First, substitute [tex]\(h = 2\)[/tex], [tex]\(k = -8\)[/tex], and [tex]\(r = 11\)[/tex] into the standard form equation:
[tex]\[ (x - 2)^2 + (y + 8)^2 = 11^2 \][/tex]
Next, calculate [tex]\(11^2\)[/tex]:
[tex]\[ 11^2 = 121 \][/tex]
So, the equation of the circle becomes:
[tex]\[ (x - 2)^2 + (y + 8)^2 = 121 \][/tex]
Let's now check which of the given options matches this equation:
1. [tex]\((x - 8)^2 + (y + 2)^2 = 11\)[/tex]
2. [tex]\((x - 2)^2 + (y + 8)^2 = 121\)[/tex]
3. [tex]\((x + 2)^2 + (y - 8)^2 = 11\)[/tex]
4. [tex]\((x + 8)^2 + (y - 2)^2 = 121\)[/tex]
Upon review, we see that the second option matches our derived equation:
[tex]\((x - 2)^2 + (y + 8)^2 = 121\)[/tex]
Therefore, the correct equation representing a circle with a center at [tex]\((2, -8)\)[/tex] and a radius of 11 is:
[tex]\[ (x - 2)^2 + (y + 8)^2 = 121 \][/tex]
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
where [tex]\((h, k)\)[/tex] is the center of the circle and [tex]\(r\)[/tex] is the radius.
Given:
- The center of the circle [tex]\((h, k)\)[/tex] is [tex]\((2, -8)\)[/tex],
- The radius [tex]\(r\)[/tex] is 11.
First, substitute [tex]\(h = 2\)[/tex], [tex]\(k = -8\)[/tex], and [tex]\(r = 11\)[/tex] into the standard form equation:
[tex]\[ (x - 2)^2 + (y + 8)^2 = 11^2 \][/tex]
Next, calculate [tex]\(11^2\)[/tex]:
[tex]\[ 11^2 = 121 \][/tex]
So, the equation of the circle becomes:
[tex]\[ (x - 2)^2 + (y + 8)^2 = 121 \][/tex]
Let's now check which of the given options matches this equation:
1. [tex]\((x - 8)^2 + (y + 2)^2 = 11\)[/tex]
2. [tex]\((x - 2)^2 + (y + 8)^2 = 121\)[/tex]
3. [tex]\((x + 2)^2 + (y - 8)^2 = 11\)[/tex]
4. [tex]\((x + 8)^2 + (y - 2)^2 = 121\)[/tex]
Upon review, we see that the second option matches our derived equation:
[tex]\((x - 2)^2 + (y + 8)^2 = 121\)[/tex]
Therefore, the correct equation representing a circle with a center at [tex]\((2, -8)\)[/tex] and a radius of 11 is:
[tex]\[ (x - 2)^2 + (y + 8)^2 = 121 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.